Self-Interference Cancellation for Simultaneous Transmit and Receive (STAR) Applications - Parker, Asif Ahmed (Department of Electrical Engineering, 2020)
Co-channel interference between transmit and receive antennas means that simultaneous transmission and reception (STAR) of signals on the same frequency is an engineering challenge when co-locating the transmit and receive channels. Due to advancements in Radio Frequency (RF) receiver and antenna hardware, as well as electromagnetic computation software, this technology is becoming more and more realisable, with applications in the fields of radar and communications. For a STAR system to be effective, high isolation (in excess of 90 dB) between transmit and receive channels is required to avoid self-interference. A lack of isolation will result in a significant reduction in the receiver sensitivity and dynamic range, reducing its ability to adequately detect incoming signals. This study involves the design and analysis of a STAR demonstrator where the theoretical and practical viability of such a system is evaluated. High isolation is achieved through the use of a combination of passive suppression, as well as analogue and digital cancellation techniques. The design consists of three cancellation layers: passive suppression, which uses a transmit antenna array to increase the transmit-receive antenna isolation through null placement; analogue cancellation, which aims to reduce self-interference by subtracting a copy of the estimated interference signal from the received signal; and digital cancellation, which uses adaptive filtering in the digital domain to further suppress residual self-interference. The demonstrator is tested in a typical real-world environment to characterise the performance of the system. The measured isolation between transmit and receive antennas is 29.4 dB. Passive suppression increases this isolation to 51.5 dB when using a four element linear transmit array. Analogue cancellation provides up to 30 dB of additional isolation, with digital cancellation providing a further 20 dB of suppression. Together, as an integrated system, the demonstrator is capable of providing a combined 101.5 dB of self-interference suppression. This clearly demonstrates that a STAR system is viable through the use of a multi-layer cancellation scheme comprising of passive suppression, analogue cancellation and digital cancellation techniques.